Solusi Tawaf Wanita Haid: Studi Pemikiran Al-Barizi, As-Subki, Ibn Taymiyyah dan Ibn Qayyim - Abdurrahman Abdurrahman; Ali Muhammad Abrori; Damanhuri Damanhuri (Lembaga Yasin AlSys, 2026)
Studies on the legal ruling of tawaf for menstruating women have been widely conducted, yet research that comprehensively synthesizes the thought of Al-Barizi, As-Subki, Ibn Taymiyyah, and Ibn al-Qayyim within a single applicative framework remains unavailable. This study aimed to explore in depth the contributions of these four scholars through a literature-based method using decontextualization and recontextualization approaches to their primary works. The findings indicated that Al-Barizi pioneered a mapping of four factual conditions experienced by female pilgrims, whereas As-Subki provided a specific recommendation for the third condition by adopting the legal solution proposed by Ibn Taymiyyah and Ibn al-Qayyim. The study concludes that Al-Barizi’s classification is highly relevant to the challenges faced by Indonesian Hajj and Umrah pilgrims, while As-Subki’s recommendation, as a Shafi‘i scholar, to apply the opinions of Ibn Taymiyyah and Ibn al-Qayyim offers a significant legal solution for menstruating female pilgrims. This study has implications for strengthening contemporary fiqh literature and provides practical guidance for the government and Hajj/Umrah organizers in mitigating obstacles to women’s worship practices in the field.